The Effect of Differences Time On The Macroscopic Picture Of Giemsa Staining Using Aquades Diluent - Muflihah, Ahdiah Imroatul; Rian Anggia Destiawan; Anas Fadli Wijaya; Lenny Yulia Widia Sari; Queen Nurul Sufi; Alisa alfiya makki; Laila Camelia (Jurnal EduHealth, 2022)
Peripheral Blood Smear Preparation (SADT) is an examination used to see the structure and number of red and white blood cells, besides giemsa staining can be used for malaria examination. The quality of giemsa staining is influenced by one of which is the soaking time of the giemsa solution. The purpose of this study was to determine the quality of slides or blood smears based on the incubation duration of giemsa staining. This research method qualitatively performed giemsa staining on blood smears with different soaking times (10 minutes, 20 minutes, 30 meinit and 40 minutes) then compared with controls. Results showed that at minutes 10 and 20 the giemsa staining showed a smooth surface and no granules, at 30 and 40 minutes the giemsa staining showed a rough surface and many granules. The conclusion of this study was that 10 and 20 min giemsa soaking showed optimal staining of blood smear preparations.